Sulfur resistance improvement of Cu-SCR catalysts

By using the catalyst composition of low SAR, copper, and rare earth elements, the problem of being susceptible to loss of existing SCR catalysts in sulfur compounds has been solved, and the sulfur resistance and water heat aging performance of catalysts are realized. And stability.

CN119343181APending Publication Date: 2025-01-21JOHNSON MATTHEY PLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380042680.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-28
Filing Date
2023-07-20
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing SCR catalysts are prone to neutralization, inactivated or reduced effectiveness when exposed to sulfur compounds, resulting in a decrease in the efficiency of exhaust gas after-treatment systems, and the desulfurization method requires high temperatures, affecting fuel economy and engine performance.

Method used

The combination of low SAR boil and copper and rare earth elements of at least 2 % of 2 % of the weight is used as a catalyst. The copper and rare earth elements are mixed into the burpester through ion exchange to form a catalyst composition with excellent sulfur resistance and water heat aging performance.

Benefits of technology

It significantly improves the sulfur resistance and water heat aging performance of catalysts, avoids the loss of catalysts and the reduction of system efficiency, while maintaining the stability of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343181A_ABST
    Figure CN119343181A_ABST
Patent Text Reader

Abstract

The invention relates to a catalyst composition. More specifically, the present invention relates to a catalyst composition comprising a low SAR zeolite, copper in an amount of at least 2% by weight; and a rare earth element. The invention also relates to a method for manufacturing the catalyst composition. The invention also relates to a catalyst article comprising the catalyst composition and a method for treating an exhaust gas comprising contacting the exhaust gas with the catalyst article comprising the catalyst composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a catalyst composition. More specifically, the present invention relates to a catalyst composition comprising a low SAR zeolite, copper in an amount of at least 2 weight percent; and a rare earth element. The present invention also relates to a method for making the catalyst composition. The present invention also relates to a catalyst article comprising the catalyst composition and a method for treating exhaust gas, the method comprising contacting the exhaust gas with the catalyst article comprising the catalyst composition. Background Art

[0002] Selective catalytic reduction (SCR) is the most effective technology for reducing NOx in exhaust aftertreatment of lean-burn engines. The SCR technology refers to a technology in which a reducing agent or reducing substance in the exhaust gas selectively reduces NOx to N2 under the action of a catalyst to avoid non-selective oxidation reactions of the reducing agent. Copper zeolite has been commercialized as an SCR catalyst due to its outstanding advantages of excellent catalytic performance and hydrothermal stability.

[0003] However, many SCR catalysts can become neutralized, deactivated, or experience a reduction in effectiveness when exposed to sulfur compounds over time. Sulfur deactivation over time is a cumulative process that limits the effective life of the catalytic components or requires periodic removal of the sulfur compounds.

[0004] The presence of sulfur reduces the efficiency of various components in the exhaust aftertreatment system. Currently known desulfurization methods require exposing the SCR catalyst to very high temperatures, which can significantly affect fuel economy, engine performance, and expose other exhaust aftertreatment system components to increased aging. Therefore, there remains a need for further improved compositions and methods for SCR aftertreatment systems.

[0005] Previous work has also found that using zeolites with low SAR and / or incorporating copper into the catalyst adversely affects catalyst stability.

[0006] The present inventors have surprisingly found that the combination of low SAR zeolite and high copper loading greatly improves the sulfur resistance compared to previous formulations without affecting the stability of the catalyst. The addition of rare earth elements can further improve the sulfur resistance, hydrothermal aging and stability of the catalyst. Summary of the invention

[0007] One aspect of the present disclosure relates to a catalyst composition comprising:

[0008] a) Low SAR zeolite;

[0009] b) copper in an amount of at least 2% by weight; and

[0010] c) Rare earth elements.

[0011] Another aspect of the present disclosure relates to a method of preparing a catalyst composition (i.e., the catalyst composition described herein), the method comprising:

[0012] (i) incorporating copper into a zeolite by ion exchange to prepare a copper-substituted zeolite; and

[0013] (ii) Incorporating rare earth elements into the copper-substituted zeolite.

[0014] Another aspect of the present disclosure relates to a catalyst article for treating exhaust gas, the catalyst article comprising the catalyst composition as described herein.

[0015] Another aspect of the present disclosure relates to an exhaust system comprising a catalyst article as described herein.

[0016] Another aspect of the present disclosure relates to a method for treating an exhaust gas, the method comprising contacting the exhaust gas with a catalyst article described herein. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Shows the effect of adding ceria to various copper-zeolite catalysts

[0018] Figure 2 Cu SCR sulfur aging using various catalyst compositions is shown. DETAILED DESCRIPTION

[0019] A first aspect of the present invention relates to a catalyst composition comprising:

[0020] a) Low SAR zeolite;

[0021] b) copper in an amount of at least 2% by weight; and

[0022] c) Rare earth elements.

[0023] The present disclosure will now be further described. In the following paragraphs, different aspects / embodiments of the present disclosure are defined in more detail. Unless there is a clear contrary description, each aspect / embodiment so defined may be combined with any other aspect / embodiment or multiple aspects / embodiments. In particular, any feature indicated as being preferred or advantageous may be combined with any other one or more features indicated as being preferred or advantageous.

[0024] Zeolite

[0025] The catalyst composition of the present invention comprises at least one zeolite. Zeolite is a structure formed by aluminum oxide and silicon dioxide, and SAR determines the reactive sites within the zeolite structure. Zeolites useful in the present invention may include small pore zeolites (e.g., zeolites with a maximum ring size of eight tetrahedral atoms), medium pore zeolites (e.g., zeolites with a maximum ring size of ten tetrahedral atoms), large pore zeolites (e.g., zeolites with a maximum ring size of twelve tetrahedral atoms), or a combination of two or more thereof.

[0026] When the catalyst composition comprises a small pore zeolite, the small pore zeolite may have a framework structure represented by a framework type code (FTC) selected from the group comprising (e.g., consisting of) ACO, AEI, AEN, AFN, AFT, AFX, ANA, APC, APD, ATT, CDO, CHA, DDR, DFT, EAB, EDI, EPI, ERI, GIS, GOO, IHW, ITE, ITW, LEV, LTA, KFI, MER, MON, NSI, OWE, PAU, PHI, RHO, RTH, SAT, SAV, SFW, SIV, THO, TSC, UEI, UFI, VNI, YUG, and ZON, or a mixture and / or combination and / or intergrowth of two or more thereof. In some embodiments, the small pore zeolite has a framework structure selected from the group comprising (e.g., consisting of) CHA, LEV, AEI, AFX, ERI, LTA, SFW, KFI, DDR, and ITE. In some embodiments, the small pore zeolite has a framework structure selected from the group comprising (eg, consisting of): CHA and AEI. The small pore zeolite can have a CHA framework structure.

[0027] When the catalyst composition comprises a medium pore size zeolite, the medium pore size zeolite may have a framework structure represented by a framework type code (FTC) selected from the group comprising (e.g., consisting of) AEL, AFO, AHT, BOF, BOZ, CGF, CGS, CHI, DAC, EUO, FER, HEU, IMF, ITH, ITR, JRY, JSR, JST, LAU, LOV, MEL, MFI, MFS, MRE, MTT, MVY, MWW, NAB, NAT, NES, OBW, -PAR, PCR, PON, PUN, RRO, RSN, SFF, SFG, STF, STI, STT, STW, -SVR, SZR, TER, TON, TUN, UOS, VSV, WEI, and WEN, or a mixture and / or intergrowth of two or more thereof. In some embodiments, the medium pore zeolite has a framework structure selected from the group comprising (e.g., consisting of) FER, MEL, MFI, and STT. In some embodiments, the medium pore zeolite has a framework structure selected from the group comprising (e.g., consisting of) FER and MFI, specifically MFI. When the medium pore zeolite has a FER or MFI framework, the zeolite may be ferrierite, silica rock, or ZSM-5.

[0028] When the catalyst composition comprises a large pore zeolite, the large pore zeolite can have a framework structure represented by a framework type code (FTC) selected from the group comprising (e.g., consisting of) AFI, AFR, AFS, AFY, ASV, ATO, ATS, BEA, BEC, BOG, BPH, BSV, CAN, CON, CZP, DFO, EMT, EON, EZT, FAU, GME, GON, IFR, ISV, ITG, IWR, IWS, IWV, IWW, JSR, LTF, LTL, MAZ, MEI, MOR, MOZ, MSE, MTW, NPO, OFF, OKO, OSI, -RON, RWY, SAF, SAO, SBE, SBS, SBT, SEW, SFE, SFO, SFS, SFV, SOF, SOS, STO, SSF, SSY, USI, UWY, and VET, or a mixture and / or interbreeding of two or more thereof. In some embodiments, the large pore zeolite has a framework structure selected from the group comprising (e.g., consisting of) AFI, BEA, MAZ, MOR, and OFF. In some embodiments, the large pore zeolite has a framework structure selected from the group comprising (e.g., consisting of) BEA, MOR, and FAU. When the large pore zeolite has a framework structure of FTC BEA, FAU, or MOR, the zeolite may be beta zeolite, faujasite, Y-type zeolite, X-type zeolite, or mordenite.

[0029] The catalyst composition of the present invention preferably comprises a zeolite with a low SAR. As used herein, a low SAR is understood to mean a zeolite with a silicon dioxide to alumina molar ratio (SAR) of between 10 and 30, more preferably about 10 to about 25, such as about 10 to about 22, about 11 to 21, about 11 to about 20, about 11 to about 18, about 12 to about 15, about 10 to about 13, about 10 to about 14, and about 12 to about 14. The silicon dioxide to alumina ratio of the zeolite can be determined by conventional analysis. The ratio is intended to represent the ratio in the rigid atomic framework of the zeolite crystal as closely as possible, and is intended to exclude silicon or aluminum in the binder or silicon or aluminum in the form of cations or other forms in the channel. Since it may be difficult to directly measure the silicon dioxide to alumina ratio of the zeolite after the zeolite is combined with a binder material, specifically an alumina binder, the ratio of these silicon dioxide to alumina is represented by the SAR of the zeolite itself, i.e. before the zeolite is combined with other catalyst components.

[0030] It has surprisingly been found that zeolites with low SAR can be used without affecting the stability of the resulting catalyst.It has been found that zeolites with low SAR in combination with the claimed copper loading and rare earth element incorporation have improved resistance to sulphur and hydrothermal aging.

[0031] copper

[0032] The catalyst composition of the present invention also includes copper. In some embodiments, copper is incorporated into zeolite, for example, by ion exchange. Copper can be present in the catalyst composition in an amount of at least 2 wt %, at least 2.5 wt %, at least 3 wt %, at least 3.5 wt %, at least 4 wt % or at least 4.5 wt %. Copper can be present in the catalyst composition in an amount of about 1 wt % to about 6 wt %, about 2 wt % to about 5.5 wt %, for example, about 3 wt % to about 5.4 wt %, about 4 wt % to about 5.3 wt %, about 4.5 wt % to about 5.2 wt %, about 4.6 wt % to about 5.1 wt % or about 4.7 wt % to about 5 wt %. In some embodiments, copper is present in the catalyst composition in an amount of about 4 wt %, about 4.5 wt %, about 4.75 wt %, about 5 wt %, about 5.25 wt % or about 5.5 wt %. The indexing of wt % is based on the weight of zeolite.

[0033] It has surprisingly been found that incorporating copper into a catalyst composition improves the performance of the catalyst without reducing the stability of the catalyst. It has been found that the use of copper in combination with a rare earth element improves sulfur resistance and hydrothermal aging while also improving the performance of the catalyst without reducing the stability of the catalyst, even when a low SAR zeolite is used.

[0034] Rare Earth Elements

[0035] Catalyst composition of the present invention contains one or more rare earth elements. Preferably, one or more rare earth elements are selected from the group comprising the following (for example, consisting of the following): La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y and Sc, including two or more combinations thereof. In a specific embodiment, the rare earth element includes Ce, Y, Zr, Mn, Fe, La, Nd and Nb. In some aspects, the rare earth element is Ce.

[0036] The rare earth element content of the catalyst composition is preferably about 2 wt % to about 5 wt %; about 2.5 wt % to about 4.8 wt %, about 3 wt % to about 4.5 wt %, about 3.5 wt % to 4.4 wt %; about 2.75 wt % to about 4.4 wt %. The reference to wt % is based on the weight of the zeolite.

[0037] Incorporation of rare earth elements has been found to improve sulfur resistance and hydrothermal aging, even when the SAR of the zeolite is low.

[0038] Preparation method

[0039] Another aspect of the present invention relates to a method for preparing a catalyst composition (i.e., the catalyst composition described herein), the method comprising:

[0040] (i) incorporating copper into a zeolite to prepare a copper-substituted zeolite; and

[0041] (ii) Incorporating rare earth elements into the copper-substituted zeolite.

[0042] Copper can be incorporated into zeolite by methods known in the art. For example, ion exchange, spray drying and cold one-pot method. Ion exchange can be carried out by blending zeolite into a solution containing a soluble copper precursor (for example, copper acetate or copper carbonate). The pH of the solution can be adjusted to induce copper ions to precipitate on or in the zeolite structure. For example, zeolite is immersed in a solution containing a soluble copper precursor (for example, copper acetate or copper carbonate) for a period of time, which is enough to allow copper ions to be incorporated into the molecular sieve structure by ion exchange. Unexchanged copper ions can be precipitated. Depending on the application, a portion of the unexchanged copper ions can be retained in the zeolite material as free metal. The copper-substituted zeolite can then be washed, dried and calcined. In a preferred alternative embodiment, the copper-substituted zeolite is directly used in the second step to incorporate rare earth elements.

[0043] Generally speaking, the ion exchange of copper in or on the zeolite can be carried out at room temperature or at a temperature up to about 100°C, up to about 90°C, up to about 80°C or up to about 70°C. For example, the ion exchange can be carried out at a temperature of 15°C to 90°C, such as 18°C ​​to 80°C, 20°C to 70°C, 21°C to 50°C, 22°C to 40°C or 25°C to 30°C. The ion exchange can be carried out for about 1 hour to 24 hours, such as 2 hours to 22 hours, 3 hours to 20 hours, 4 hours to 15 hours or 5 hours to 10 hours. The ion exchange can be carried out at a pH of less than 9, such as less than 8, less than 7, less than 6, less than 5, less than 4 or less than 3. In a preferred example, the pH of the ion exchange is between 2 and 5, or between 3 and 4. The resulting copper-substituted zeolite material is preferably used directly in the second step to incorporate rare earth elements. In an alternative embodiment, the resulting copper-substituted zeolite is dried at about 100°C to 120°C. In some embodiments, the copper-substituted zeolite material is dried for 5 to 20 hours, such as 8 to 18 hours, such as 10 to 15 hours.The copper-substituted zeolite material may then be calcined at a temperature of at least about 550°C.

[0044] The copper may be present as an extra-framework metal located within the zeolite and / or on at least a portion of the surface of the zeolite.

[0045] Copper may be present as a counter ion at the ion exchange sites of the framework structure.

[0046] Copper can be incorporated into the zeolite separately from the incorporation of the rare earth element. The method of preparing the catalyst composition may include incorporating the rare earth element and incorporating copper in separate processes before or after the incorporation of the rare earth element. In an alternative embodiment, copper can be incorporated into the zeolite simultaneously with the rare earth element.

[0047] Rare earth elements (e.g., rare earth elements as described herein) can be incorporated into zeolites (e.g., copper-substituted zeolites as described herein) so that they are present as counterions at the ion exchange sites of the framework structure. Rare earth elements can exist as extra-framework elements, which are located in the zeolite and / or at least a portion of the zeolite surface, do not include aluminum, and do not include atoms constituting the molecular sieve framework. Rare earth elements can be added to zeolites (e.g., copper-substituted zeolites as described herein) via any known techniques such as ion exchange, spray drying, and cold one-pot methods. Preferably, rare earth elements are incorporated by ion exchange.

[0048] The method for preparing the catalyst composition may include incorporating rare earth elements into zeolites (e.g., copper-substituted zeolites as described herein) by ion exchange. Ion exchange can be performed by blending zeolites (e.g., copper-substituted zeolites as described herein) into a solution containing a soluble precursor of rare earth elements. The pH of the solution can be adjusted to induce catalytically active rare earth element cations to precipitate onto or within the zeolite structure. For example, zeolites (e.g., copper-substituted zeolites as described herein) are immersed in a solution containing a soluble precursor of rare earth elements for a period of time, which is sufficient to allow catalytically active rare earth cations to be incorporated into the molecular sieve structure by ion exchange. Unexchanged rare earth ions can be precipitated. Depending on the application, a portion of the unexchanged ions can be retained in the zeolite material as free metals. The rare earth-substituted zeolite can then be washed, dried and calcined. In a preferred alternative embodiment, the resulting rare earth-substituted zeolite is directly used to form a carrier coating.

[0049] In a specific embodiment, the zeolite (e.g., a copper-substituted zeolite as described herein) is immersed in a solution containing cerium acetate or cerium carbonate for a period of time sufficient to allow catalytically active cerium cations to be incorporated into the molecular sieve structure by ion exchange. Unexchanged cerium ions can be precipitated out. Depending on the application, a portion of the unexchanged ions can be retained in the zeolite material as free cerium. The cerium-substituted zeolite can then be washed, dried and calcined. In a preferred alternative embodiment, the resulting cerium-substituted zeolite is directly used to form a carrier coating.

[0050] Generally speaking, the incorporation of rare earth elements into or onto zeolites to form a catalyst composition can be carried out at room temperature or at a temperature up to about 80°C. For example, the incorporation of rare earth elements can be carried out at a temperature of 15°C to 80°C, such as 18°C ​​to 70°C, 20°C to 60°C, 21°C to 50°C, 22°C to 40°C, or 25°C to 30°C. In a preferred embodiment, the incorporation of rare earth elements is carried out at room temperature (e.g., a temperature of 15°C to 30°C, 16°C to 28°C, 17°C to 25°C, 18°C ​​to 23°C, or 19°C to 21°C). Ion exchange can be carried out for about 1 hour to 24 hours, such as 2 hours to 22 hours, 3 hours to 20 hours, 4 hours to 15 hours, or 5 hours to 10 hours. Ion exchange can be carried out at a pH of less than 9, such as less than 8, less than 7, less than 6, less than 5, less than 4, or less than 3. In a preferred example, the pH of the ion exchange is between 2 and 5, or between 3 and 4.

[0051] In an alternative embodiment, the zeolite is combined with water and a copper source (e.g., copper carbonate) is added. The resulting mixture is placed at room temperature (e.g., 15°C to 25°C, 16°C to 24°C, 17°C to 23°C, 18°C ​​to 22°C, or 19°C to 21°C) for a suitable period of time (e.g., between 1 hour and 24 hours, e.g., 2 hours to 22 hours, 3 hours to 20 hours, 4 hours to 15 hours, or 5 hours to 10 hours). Rare earth elements (e.g., in the form of rare earth salts such as cerium acetate or cerium carbonate) may then be added to form a catalyst composition.

[0052] The catalyst composition as described herein can then be formulated in a washcoat. In addition to the catalyst composition, the washcoat composition can also include: (i) one or more binders selected from the group comprising (e.g., consisting of) alumina, silica, (non-zeolitic) silica-alumina, naturally occurring clays, TiO2, ZrO2, and SnO2, and / or (ii) one or more rheology modifiers (e.g., a rheology modifier such as Natrosol, TEAOH (tetraethylammonium hydroxide), Dispex, or ammonia).

[0053] The washcoat may be applied to a substrate, such as a metal or ceramic flow-through monolith substrate or a filtering substrate, for example a substrate comprising, for example, a wall flow filter or a sintered metal or partial filter. Preferably, the resulting coated substrate is dried and calcined. Preferably, the coated substrate is dried at about 100° C. to 120° C. Preferably, the coated substrate is dried for 15 minutes to 2 hours, for example 20 minutes to 1 hour. The dried coated substrate may then be calcined at a temperature of 400° C. to 800° C., preferably 450° C. to 750° C., for example about 500° C.

[0054] Catalyst products

[0055] In another aspect of the present invention, there is provided herein a catalyst article for exhaust gas, wherein the catalyst article comprises a catalyst composition as described herein or obtained by a method as described herein.

[0056] The catalyst composition (e.g., a catalyst composition as described herein) may be in the form of a carrier coating, preferably a carrier coating suitable for coating a substrate, such as a metal or ceramic flow-through monolithic substrate or a filtering substrate, for example a substrate comprising, for example, a wall-flow filter or a sintered metal or a partial filter. Therefore, another aspect of the present invention is a carrier coating comprising a catalyst composition as described herein. In addition to the catalyst composition, the carrier coating composition may also include one or more binders selected from the group comprising (e.g., consisting of) alumina, silica, (non-zeolite) silica-alumina, naturally occurring clays, TiO2, ZrO2, and SnO2. Another aspect of the present invention is a catalyst article comprising a substrate and a catalyst composition as described herein, which can be applied as a carrier coating.

[0057] The preferred substrate for use is a monolith with a so-called honeycomb geometry, which includes a plurality of adjacent parallel channels, each of which generally has a square cross-sectional area. The honeycomb shape provides a large catalytic surface with a minimum overall size and pressure drop. The catalyst composition can be deposited on a flow-through monolith substrate (e.g., a honeycomb monolith catalyst carrier structure with many small parallel channels axially passing through the entire component) or a filter monolith substrate such as a wall-flow filter. In another embodiment, the catalyst composition is formed as an extruded catalyst. Preferably, the catalyst composition is coated on the substrate in an amount sufficient to reduce the NOx contained in the exhaust gas flow flowing through the substrate. In certain embodiments, at least a portion of the substrate may also contain a platinum group metal, such as platinum (Pt), to oxidize ammonia in the exhaust gas flow or to perform other functions, such as converting CO into CO2.

[0058] The catalyst article as described herein preferably comprises a honeycomb monolith body comprising a catalyst composition (eg, a catalyst composition as described herein), preferably as a washcoat layer thereon.

[0059] Exhaust system and method

[0060] According to another aspect, an exhaust system is provided, the exhaust system comprising a catalyst article as described herein and, optionally, an internal combustion engine. The internal combustion engine may be a diesel engine, a lean-burn gasoline engine, or an engine powered by liquid petroleum gas or natural gas. Preferably, the internal combustion engine is a diesel engine. The catalyst article may be arranged downstream of the engine to treat the exhaust gas discharged from the engine.

[0061] According to yet another aspect of the present invention, there is provided a method for treating an exhaust gas, the method comprising contacting the exhaust gas with the catalyst article described herein.

[0062] Although the preferred embodiments of the present invention have been described in detail herein, it will be apparent to those skilled in the art that various changes may be made therein without departing from the scope of the invention or the appended claims.

[0063] The invention will now be further described with reference to the following non-limiting examples and accompanying figures.

[0064] Example

[0065] General approach

[0066] Zeolite, ZEO (CHA zeolite with SAR of 14) or ZEO2 (CHA zeolite with SAR of 23) was mixed with water and copper acetate was added to the reaction mixture. The reaction mixture was heated to 70°C for 4 hours. The reaction mixture was cooled and then water dispersible boehmite alumina was added, followed by cerium acetate, then natrosol and the pH was adjusted to >3.8 with TEAOH.

[0067] Example 1 - Varying Cu and rare earth loadings

[0068] The Cu-zeolite catalyst was prepared by impregnating zeolite powder with acetic acid Cu(II) solution to achieve a Cu loading between 2 wt% and 5.5 wt%. Ce was incorporated into the Cu-zeolite catalyst to achieve 25 g / ft 3 Up to 200g / ft 3 Total carrier coating loading is 2.4 g / in 3 Up to 3g / in 3 .

[0069] The following catalysts were prepared :

[0070]

[0071] SCAT Test

[0072] The Scat test was evaluated at four temperature points (175°C, 200°C, 250°C and 600°C) with a temperature ramp of 600°C between each stage. During the test, 500 ppm NOx was evaluated at 1.5 ALPHA. The test was run for a set amount of time or until 20 ppm ammonia slip occurred, whichever occurred first. NOx conversion, N2O selectivity and NH3 storage were evaluated at the four temperature points. The results are shown in Figure 1 middle.

[0073] Figure 1The effect of different ceria loading and copper loading is shown for fresh and aged (650°C for 50 hours). For performance Δ, the best result is Cu (4.75%) ZEO Ce (188 g / ft 3 Cu(4 wt%) ZEO is a reference example of ZEO with 4 wt% Cu loading. ZEO is a CHA zeolite framework with a SAR of 14.

[0074] Example 2 - Varying the Sulfur Loading :

[0075] Sulfur loading / doping was performed on a syngas bench plant by subjecting fully coated SCR ceramic monolith catalyst samples (1×3”) with a Pt-based DOC (1×1”) upstream of the SCR catalyst under consideration to a predetermined number of defined cycles of a SO2 aged gas mixture (Table 1). Each sulfation “SOx cycle” consisted of ramping to 525°C, cooling to 200°C, and then cycling between 200°C and 350°C three times, with SO2 injection only during the cycling phase to target a sulfur exposure of approximately 0.45 g / L per cycle. Prior to subjecting each catalyst sample to a predetermined number of “SOx cycles”, the actual sulfur exposure during each “SOx cycle” was calculated by using a blank core as a sulfur inlet check on an aged gas mixture with a target of 7.5 ppm SO2.

[0076] gas concentration NO 100ppm <![CDATA[NH3]]> 0ppm <![CDATA[SO2]]> 7.5ppm <![CDATA[O2]]> 10% <![CDATA[H2O]]> 5% <![CDATA[CO2]]> 8% <![CDATA[N2]]> margin

[0077] Table 1 - SO2 Aging Gas Mixture

[0078] SCR performance evaluation after sulfation testing

[0079] After checking a predetermined number of "SOx cycles" of known sulfur exposure / loading via the SO2 inlet check (described above), the SCAT was subjected to an SCR performance evaluation test using an SCR evaluation gas mixture (Table 2), using only the "loaded" SCR sample. The SCR performance test consisted of ramping to a set temperature (450°C, 500°C, 530°C), cooling and holding at 200°C after each ramp, and evaluating in the SCR evaluation gas mixture at 200°C until 20 ppm NH3 slip occurred. The results are shown in Figure 2 In. ZEO2 is a CHA zeolite with a SAR of 23.

[0080] gas concentration NO 500ppm <![CDATA[NH3]]> 750ppm CO 350ppm <![CDATA[O2]]> 10% <![CDATA[H2O]]> 5% <![CDATA[CO2]]> 8% <![CDATA[N2]]> margin

[0081] Table 2 - SCR Evaluation Gas Mixture

[0082] Figure 2Cu SCR sulfur aging using various catalyst compositions is shown. The figure shows that the addition of rare earth elements improves sulfur resistance and hydrothermal aging.

Claims

1. A catalyst composition, comprising: a) Low SAR zeolites; b) copper in an amount of at least 2% by weight; and c) Rare earth elements.

2. The catalyst composition according to claim 1, wherein the zeolite has a SAR between 10 and 25, preferably from 11 to 21.

3. A catalyst composition according to claim 1 or claim 2, wherein the amount of copper is at least 2.5 wt%, preferably at least 3 wt%, more preferably at least 4 wt%.

4. The catalyst composition according to any preceding claim, wherein the rare earth element is selected from the group comprising La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y and Sc, preferably wherein the rare earth element is selected from the group comprising Ce, Y, Zr, Mn, Fe, La, Nd and Nb.

5. The catalyst composition according to any preceding claim, wherein the rare earth element is present in an amount of 2 to 5 wt%, preferably 2.75 to 4.5 wt%.

6. The catalyst composition according to any preceding claim, wherein the zeolite is a small pore zeolite, preferably wherein the small pore zeolite has a CHA or AEI framework structure type.

7. A method for preparing a catalyst composition according to any one of claims 1 to 6, the method comprising: (i) incorporating copper into zeolite to prepare a copper-substituted zeolite; as well as (ii) Incorporating rare earth elements into the copper-substituted zeolite.

8. A catalyst article for an exhaust system, comprising a catalyst composition according to any one of claims 1 to 6 or obtainable by a process according to claim 7.

9. An exhaust system comprising the catalyst article according to claim 8 and, optionally, an internal combustion engine, preferably a diesel engine.

10. A method for treating exhaust gas, the method comprising contacting the exhaust gas with the catalyst article according to claim 8.